Serum soluble suppression of tumorigenicity‐2 level associates with severity of pulmonary hypertension associated with uncorrected atrial septal defect. (1st May 2020) - Pratama, Reza S.; Hartopo, Anggoro B.; Anggrahini, Dyah W.; Dewanto, Vera C.; Dinarti, Lucia K.
Abstract : Uncorrected atrial septal defect undergoes right ventricle chronic volume overload which may lead to pulmonary hypertension and Eisenmenger Syndrome. The soluble suppression of tumorigenicity‐2 is a left ventricle strain biomarker; however, its role in right ventricle strain is unclear. This study aimed to investigate the implication of serum soluble suppression of tumorigenicity‐2 in adult uncorrected atrial septal defect. This was a cross‐sectional study. We enrolled 81 adult uncorrected secundum atrial septal defect patients. Clinical and hemodynamic data were collected. Serum samples were withdrawn from the pulmonary artery during right heart catheterization. Serum soluble suppression of tumorigenicity‐2 and NT‐proBNP levels were measured. Subjects were divided into three groups based on clinical and hemodynamic severity. The correlation of soluble suppression of tumorigenicity‐2 with patients' data and comparison among groups were analyzed. A p value <0.05 was considered statistically significant. Results showed that, there were significant correlations between serum soluble suppression of tumorigenicity‐2 and mean pulmonary artery pressure ( r  = 0.203, p  = 0.035) and right ventricle end‐diastolic diameter ( r  = 0.203, p <0.05). Median serum soluble suppression of tumorigenicity‐2 level was incrementally increased from group I (atrial septal defect and no‐pulmonary hypertension), group II (left‐to‐right atrial septal defect and pulmonary hypertension), to group III (Eisenmenger Syndrome): (17.4 ng/mL, 21.8 ng/mL, and 29.4 ng/mL, respectively). A post‐hoc analysis showed that serum soluble suppression of tumorigenicity‐2 level was significantly different between groups I and III ( p  = 0.01). Serum N terminal pro brain natriuretic peptide (NT‐proBNP) level was consistently associated with worse clinical and hemodynamic parameters. No correlation was found between serum soluble suppression of tumorigenicity‐2 and NT‐proBNP level. In conclusion, serum soluble suppression of tumorigenicity‐2 level had significant positive correlation with mean pulmonary artery pressure and right ventricle end‐diastolic diameter in uncorrected secundum atrial septal defect patients. Higher serum soluble suppression of tumorigenicity‐2 level was associated with the presence of pulmonary hypertension and Eisenmenger Syndrome in uncorrected secundum atrial septal defect patients.